2019
DOI: 10.1080/17461391.2019.1635650
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lactate kinetics underpin soccer performance adaptations to cycling‐based sprint interval training

Abstract: In adolescent soccer, 23% of the distance covers happens at speeds above onset of blood lactate accumulation which suggests that lactate kinetics may be important for soccer performance. We sought to determine the effectiveness of sprint interval training (SIT) on changing performance and lactate kinetics in adolescent soccer players. Thirteen elite soccer academy players (age 15 ± 0.5y) underwent baseline testing (0-10m and 10-20m sprint performance, Wingate anaerobic Test (WaNT) with blood lactate measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Nevertheless, performing the WAnT might be contraindicated during congested fixture periods or periods of intense training ( Freitas et al, 2021 ). In such periods, additional exercise testing fatigue would be undesirable considering that WAnT might lead to blood lactate concentration higher than 11 mmol.L –1 in soccer players ( Keir et al, 2013 ; Thom et al, 2020 ) and athletes of other sport ( Jemni et al, 2006 ), and the use of surrogate measures of short-term muscle power might be an alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, performing the WAnT might be contraindicated during congested fixture periods or periods of intense training ( Freitas et al, 2021 ). In such periods, additional exercise testing fatigue would be undesirable considering that WAnT might lead to blood lactate concentration higher than 11 mmol.L –1 in soccer players ( Keir et al, 2013 ; Thom et al, 2020 ) and athletes of other sport ( Jemni et al, 2006 ), and the use of surrogate measures of short-term muscle power might be an alternative.…”
Section: Introductionmentioning
confidence: 99%
“…In many team sports, practitioners and rehabilitation staff will choose training practices that simultaneously reduce musculoskeletal load while promoting appropriate central and peripheral stimuli. The use of cycle-based HIIT has been used with team sport athletes over periods of 2–6 weeks to improve intermittent running and cycling performance (Jones et al 2015 ; Hamlin et al 2017 ; Beard et al 2019 ; Thom et al 2020 ), while others have reported no effect of 5 weeks of cycle-based HIIT on running performance (Goods et al 2015 ). Cycling might be adopted for athletes who require more careful load management, e.g., during rehabilitation after injury or in the days after match play, or to provide alternative training stimuli (Mallol et al 2020 ; Thom et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of cycle-based HIIT has been used with team sport athletes over periods of 2–6 weeks to improve intermittent running and cycling performance (Jones et al 2015 ; Hamlin et al 2017 ; Beard et al 2019 ; Thom et al 2020 ), while others have reported no effect of 5 weeks of cycle-based HIIT on running performance (Goods et al 2015 ). Cycling might be adopted for athletes who require more careful load management, e.g., during rehabilitation after injury or in the days after match play, or to provide alternative training stimuli (Mallol et al 2020 ; Thom et al 2020 ). However, the application of cycle-based training with team sport athletes seems to have been applied without any direct comparison of the physiological and neuromuscular responses when compared to that from similar running-based HIIT approaches.…”
Section: Introductionmentioning
confidence: 99%